Exploring Moral and Multicultural Diversity: A New Islamic Education Curriculum - Dewantara, Muhammad Iqbal; Rahmatullah, Asep (Jurnal Pendidikan Islam, 2025)
Islamic Religious Education (PAI) in Indonesia is often criticized for focusing too much on ritual doctrine and failing to instill substantive moral reasoning and applicable diversity attitudes, exacerbating social ethical challenges. This study aims to develop and test the effectiveness of a Multicultural PAI Curriculum as a solution that integrates morality and diversity. Using an Exploratory Sequential Mixed Methods (Qual→Quan) design, the Multicultural PAI Curriculum was constructed based on Contextual Ethics and Nusantara Islamic Studies, then tested through a quasi-experiment (N=70 students) with MANCOVA analysis to measure Moral Reasoning and Attitude Tolerance. The novelty of this study is the success of presenting an operational model of PAI as a tested Applied Ethics Curriculum, different from conventional legalistic studies. The results show that the Multicultural PAI Curriculum is significantly superior (Þ<0.01) in improving both variables, filling a theoretical gap in the applied PAI literature. In conclusion, the Multicultural Insight PAI Curriculum is effective as a new transformative PAI model, urging national curriculum reform so that PAI becomes a pillar of ethical and pro-diversity character formation.